The Effects of The Fed’s Interest Rate, US Obligation Yield, DJIA, Inflation, Exchange Rate, and Stock Trading Volume on Idx Composite in Indonesia During the 2021-2024 Period - Susanti, Ratna Puji; Sakti, Rachmad Kresna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The global economic crisis was triggered by an increase in global inflation due to the rise in demand for goods and an increase in commodity prices due to the geopolitical turmoil in Russia and Ukraine. It affects the macroeconomics of various countries, especially the United States which has a major influence on global markets by responding to changes in the American macroeconomy it affects the Indonesian macroeconomy and has an impact on the Indonesian capital market because Indonesia has a dependence on foreign capital flows. The purpose of this study is to determine how the influence of the Fed Interest Rate, Dow Jones Industrial Average (DJIA), US Bond Yield, Inflation, Exchange Rate, and stock trading volume on the IDX Composite in Indonesia. The research method in this study used multiple linear regression analysis. The findings of this study indicate that the Fed Interest Rate has a significant negative effect on the IDX Composite, US Bond Yield, DJIA, Inflation and Stock Trading Volume have a significant positive effect on the IDX Composite. However, the findings of the Exchange Rate do not affect the IDX Composite.